Infection by Austrodiplostomum compactum metacercariae in fish from the Nova Avanhandava reservoir, Tiete river, São Paulo State, Brazil. - Paes, Jaciara Vanessa Kruger; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo Jose (Universidade Estadual de Maringa, 2010)
This study aimed to evaluate the infection by the Austrodiplostomum compactum metacercariae in fishes from the Nova Avanhandava Reservoir, low Tiete river, São Paulo State, Brazil. The parasites were collected from eye (aqueous and vitreous humor), fixed in AFA solution and stained with carmine. The morphometric analysis was performed using a computerized system for analysis of images QWin Lite 2.5 (Leica). Prevalence, mean intensity of infection and abundance of infected fish were calculated. of the 22 species of fish registered, five were infected by metacercariae: Hoplias malabaricus, Metynnis maculatus, Plagioscion squamosissimus, Satanoperca pappaterra and Schizodon imparts. of the 627 fish evaluated, 34% were infected. A higher prevalence was observed in P. sqnamosissionis and S. pappaterra. Schizodon nasutus and M. maculatus are new hosts reported for A. compactum metacercariae.